ASSOCIATIONS BETWEEN PERCEIVED CAMPUS MENTAL HEALTH CULTURE AND STUDENTS’ QUALITY OF LIFE: A CROSS-SECTIONAL AND CORRELATIONAL STUDY - Akmalova, Diyora (Nazarbayev University School of Medicine, 2025)
Introduction: Campus mental health culture may significantly influence students’ quality of life. While existing literature reveals that perceived campus mental health culture (stigma, attitudes, and barriers to treatment) may play a complex role in influencing students’ help-seeking behavior, only a few studies have examined how these factors relate to students’ health-related quality of life. Aim/s: The following study analyzed the relationships between demographic variables, campus mental health culture (stigma, attitudes, and barriers to treatment), and quality of life. Methods: The study took place at the Nazarbayev University campus and involved 372 samples. It utilized a cross-sectional survey design. Students were recruited via email invitations, social media posts, and posters through a convenience sampling method from January to March 2025. Data was gathered online through a self-reported questionnaire, with the following tools being used: the Short Form-12v2 Health Survey (SF-12v2), the Discrimination-Devaluation Scale (DDS), the Attitudes toward Seeking Professional Psychological Help-Short Form (ATSPPHSF), and the External Demands subscale of the Barriers to Treatment Participation Scale (BTPS). Results: The study revealed that personal mental health history and gender were stronger predictors of mental health outcomes, while the barriers to treatment had a noteworthy impact on the physical outcomes of quality of life. Conclusions: Our findings suggest that interventions to improve students' quality of life may benefit from addressing common obstacles to treatment (e.g., scheduling, academic obligations, and fatigue). Also, targeted strategies are needed to reflect socio-demographic differences that relate to quality of life, stigma, help-seeking attitudes, and barriers to promote more equitable access to care.
Keywords: Quality of life; university students; campus; mental health culture; attitudes; stigma; treatment barriers; type of access: embargo